2021
DOI: 10.1152/ajpheart.00709.2020
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of age-related blood-brain barrier disruption and cerebromicrovascular rarefaction in mice by longitudinal intravital two-photon microscopy and optical coherence tomography

Abstract: Age-related blood-brain barrier disruption and cerebromicrovascular rarefaction contribute importantly to the pathogenesis of both vascular cognitive impairment and dementia (VCID) and Alzheimer's disease (AD). Recent advances in geroscience research enable development of novel interventions to reverse age-related alterations of the cerebral microcirculation for prevention of VCID and AD. To facilitate this research there is an urgent need for sensitive and easy-to-adapt imaging methods, which enable longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 143 publications
3
35
0
Order By: Relevance
“…We also confirmed that age-related impairment of NVC responses is also associated with decreased basal cerebral blood flow, suggesting shared etiology (e.g., endothelial dysfunction [53,54]). Experimental studies suggest that aging is associated with cerebromicrovascular rarefaction [55][56][57], which likely also attenuates cerebral blood flow. Agerelated damage of the neurovascular unit, especially injury of capillary endothelial cells and pericytes, both of which have been suggested to contribute to basal cerebral blood flow as well as neurovascular coupling can underly our clinical observations.…”
Section: Discussionmentioning
confidence: 99%
“…We also confirmed that age-related impairment of NVC responses is also associated with decreased basal cerebral blood flow, suggesting shared etiology (e.g., endothelial dysfunction [53,54]). Experimental studies suggest that aging is associated with cerebromicrovascular rarefaction [55][56][57], which likely also attenuates cerebral blood flow. Agerelated damage of the neurovascular unit, especially injury of capillary endothelial cells and pericytes, both of which have been suggested to contribute to basal cerebral blood flow as well as neurovascular coupling can underly our clinical observations.…”
Section: Discussionmentioning
confidence: 99%
“…The BBB is a functional part of the NVU and is critical for the protection of neurons, maintenance of homeostasis, and the integrity of the brain itself ( 19 , 237 , 238 ). BBB dysfunction is one of the hallmarks of the aging brain, in both humans and animal models ( 19 , 33 , 34 , 239 241 ). The BBB comprises brain capillary endothelial cells with support from pericytes embedded in the basement membrane and astrocytes.…”
Section: Role Of Gh/igf-1 In Regulation Of Cerebrovascular Functionmentioning
confidence: 99%
“…In addition to large vessel disease, age-related VCID is associated with a wide variety of microvascular pathologies ( 9 17 ). Microvascular contributions to cognitive decline and dementia include microvascular rarefaction ( 18 21 ), impaired endothelial regulation of cerebral blood flow ( 5 , 22 30 ), disruption of the blood brain barrier (BBB) ( 19 , 31 36 ), decreased neurovascular coupling (NVC) ( 37 41 ), cerebral microhemorrhages (CMH) ( 42 44 ), lacunar infarcts ( 45 49 ), increased pulsatility ( 50 53 ) and small vessel disease-related white matter damage ( 54 57 ), and amyloid pathologies ( 58 62 ). Critically, the severity of age-related increases in microvascular pathological alterations predict cognitive decline in aging ( 44 , 63 , 64 ), leading to great interest in understanding the associated cellular and molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Those effects were ameliorated in mice with endothelial specific loss of the complement C3a receptor. Nyul-Toth et al [ 128 ] have performed longitudinal studies in mice using intravital two-photon microscopy and optical coherence tomography to monitor changes in BBB permeability and brain vascularity during aging. They found that the permeability of single capillaries increased with age while capillary density decreased.…”
Section: Neurological Disordersmentioning
confidence: 99%